2004
DOI: 10.1111/j.0001-7272.2004.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage is a metazoan tissue; integrating data from nonvertebrate sources

Abstract: Connective tissues are responsible for much of the variation in morphology that we see today. Cartilage is a type of connective tissue that is often considered to be restricted to vertebrates, however, cartilaginous tissues are also found within invertebrates. Unfortunately, most definitions and classification schemes for cartilages suffer from a strong vertebrate bias, severely hampering the efforts of those who have attempted to include invertebrate tissues as cartilage. To encompass all types of cartilage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 64 publications
1
36
0
1
Order By: Relevance
“…It has been suggested that the notochord may represent a primitive form of cartilage, based on their many shared structural, cellular, and molecular properties, and that vertebrate chondrocytes may have evolved from notochordal cells (21,22). In gnathostomes, the notochord and͞or notochordal sheath expresses most of the vertebrate clade A fibrillar collagen genes (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the notochord may represent a primitive form of cartilage, based on their many shared structural, cellular, and molecular properties, and that vertebrate chondrocytes may have evolved from notochordal cells (21,22). In gnathostomes, the notochord and͞or notochordal sheath expresses most of the vertebrate clade A fibrillar collagen genes (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that duplication and divergence of the clade A collagen genes in stem-group vertebrates may have facilitated the evolutionary diversification of chondrocytes and notochordal cells. This hypothesis deals specifically with the origin of vertebrate chondrocytes, and it is important to note that cartilage is also found in several invertebrates, including cephalopods, snails, and horseshoe crabs (1,21). Future work on the molecular basis of invertebrate chondrogenesis should reveal whether fibrillar collagens also were used in these independent evolutionary events.…”
Section: Discussionmentioning
confidence: 99%
“…In fact within the invertebrates that have been investigated, a spectrum of histological tissues that parallels the diversity found within modern fishes is found (Cole and Hall, 2004b). Cartilages found within Cephalopod mollusks are remarkably similar to vertebrate hyaline cartilage at a histological level (Cole and Hall, 2004a). On close inspection, one can find one significant difference between vertebrate hyaline cartilage and that found within the cephalopod -the extra-cellular matrix of the cephalopod, in addition to the chondrocytes, is riddled with small canals -through which pass thin extensions of chondrocyte processes which retain connections between one another (Bairati et al, 1998;Leone et al, 2004;Cole and Hall, 2009).…”
Section: Ag Colementioning
confidence: 89%
“…The affinity of the notochord to cartilage remains debatable; Cole and Hall (2004a) argue for its inclusion as a vesicular cartilage, whereas Witten et al (2010) consider the notochord as "cartilage-related" (See Hall, 2005, for further discussion). Chondrocytes, or "chondrocyte-like" cells are predominant Fig.…”
Section: Ag Colementioning
confidence: 99%
See 1 more Smart Citation